Peran Lembaga Amil Zakat Al-Wasliyah Beramal (LAZ Washal) Dalam Peningkatan Jumlah Muzakki Di Kota Medan - Annisari Annisari; Nurul Inayah (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
The urgency of zakat lies in the success or decline of zakat institutions in managing zakat funds. To distribute and distribute zakat from muzakki to mustahik, an official, professional, responsible and trustworthy amil zakat institution is needed, then the role of the function for the institution will be maximized which is have a positive impact on Muslims at a macro level. What remains to be underlined is that the role of the management function of the amil zakat institution has not been maximized, besides the need for guidance in terms of shari'ah and development of zakat and public trust in the administration of zakat. In addition, the tendency of muzakki to channel their zakat funds directly to mustahik causes the mapping of the distribution to be maximally uneven. Besides that, it seems to forget the management function of the amil zakat institution as an official institution in the collection and distribution of zakat. This study aims to answer two main problems, firstly what is the role of LAZ Washal Al-Wasliyah Beramal in attracting prospective muzakki to distribute zakat, infaq and alms to amil zakat institutions. Second, the extent to which the role of LAZ Washal Al-Wasliyah Charity in socializing the amil zakat institution to the public. This study uses descriptive analysis method, with the type of research Field Research (field research) through interviews (interviews), documentation and observation (observations). Urgensi zakat terletak pada keberhasilan atau kemunduran institusi zakat dalam mengelola dana zakat. Dalam proses penyaluran dan pendistribusian dari muzakki ke mustahik diperlukan andil lembaga amil zakat resmi, professional, bertanggungjawab dan amanah, sehingga andil dari lembaga tersebut dinilai maksimal yang nantinya memili dampak positif terhadap umat Islam secara makro. Perihal yang harus digaris bawahi ialah peran fungsi manajemen dari lembaga amil zakat yang dinilai belum maksimal disamping masih diperlukannya bimbingan dari segi syari'ah maupun perkembangan zakat serta kepercayaan masyarakat terhadap penyelenggaraan zakat. Selain itu, kecenderunan muzakki menyalurkan langsung dana zakatnya kepada mustahik menyebabkan pemetaan dalam pendistribusian tidak merata secara maksimal. Daripada itu, seperti melupakan fungsi peranan manajemen dari lembaga amil zakat sebagai lembaga resmi dalam penghimpunan dan pendistribusian zakat. Penelitian ini bertujuan untuk menjawab dua permasalahan utama, pertama sejauh mana peran LAZ Washal Al-Wasliyah Beramal dalam menarik minat calon muzakki untuk menyalurkan zakat, infak dan sedekah ke lembaga amil zakat. Kedua, sejauh mana peran LAZ Washal Al-Wasliyah Beramal dalam mensosialisasikan lembaga amil zakat kepada masyarakat. Penelitian ini menggunakan metode analisis deskriptif, dengan jenis penelitian Field Research (penelitian lapangan) melalui interview (wawancara), dokumentasi dan observasi (pengamatan). Kata Kunci: Amil Zakat, Muzakki, Peran Fungsi, Zakat.